Pengukuran E-learning Readiness pada Mahasiswa Sebagai Upaya Penerapan Pembelajaran Jarak Jauh Masa Pandemi COVID-19 - Aprilia Sulistyohati (Universitas Hamzanwadi, 2020)
One of the efforts to reduce COVID-19 cases is a Distance Learning (PJJ) system for all levels of education. This study aims to determine the e-learning readiness of Cikarang University. Measurement of e-learning readiness implementation is carried out using the ELR framework. In this study, the ELR framework has consist of 4 main components, that are technology, innovation, people and self-development. This research was conducted on student in Cikarang University. Collecting data used structured interview with the campus management and then distributing questionnaires. The data processing used descriptive statistical techniques then mapped the e-learning Readiness index. The results of this study is to show that the Faculty of Engineering Cikarang University in the third level (ready) in implementing e-learning, but still requires improvement and preparation in several aspects to achieve success in implementing e-learning. Some recommendations are proposed for Cikarang University, that is the availability of an e-learning system that can fulfill students' need for learning and assigning. In addition, the campus is expected to be able to conduct socialization and training on e-learning to students so that it makes students understand the e-learning system at Cikarang University.